Molecular typing and antibiotic resistance patterns among clinical isolates of Acinetobacter baumannii recovered from burn patients in Tehran, Iran - Maleki, Abbas; Kaviar, Vahab Hassan; Koupaei, Maryam; Haddadi, Mohammad Hossein; Kalani, Behrooz Sadeghi; Valadbeigi, Hassan; Karamolahi, Somayeh; Omidi, Nazanin; Hashemian, Marziyeh; Sadeghifard, Nourkhoda; Mohamadi, Jasem; Heidary, Mohsen; et al. (Frontiers in Microbiology, 2022)
Acinetobacter baumannii (A. baumannii) is now considered a highly resistant pathogen to various types of antibiotics. Therefore, tracking the source of its prevalence and continuous control is crucial. This study aimed to determine antibiotic resistance and perform various molecular typing methods on clinical isolates of A. baumannii isolated from hospitalized patients in Shahid Motahari Burn Hospital, Tehran, Iran. Hospital isolates were confirmed by phenotypic and molecular methods. Then the sensitivity to different antibiotics was determined using the minimum inhibitory concentration (MIC) method. In order to perform molecular typing, three-locus dual assay multiplex polymerase chain reaction (PCR), multiple-locus variable number tandem repeats (VNTRs) analysis (MLVA), and multilocus sequence typing (MLST) methods were used. Among the 60 isolates collected, the frequencies of multidrug-resistant (MDR) and extensively drug-resistant (XDR) isolates were 90% and 10%, respectively. The most effective antibiotics were colistin with 100% and tigecycline with 83.33% sensitivity. Isolates were 100% resistant to piperacillin/tazobactam and cephalosporins, and 68.3% were resistant to carbapenem. The results of multiplex PCR showed five groups that international clone I (IC I) and IC II were the most common. The MLVA method identified 34 MLVA types (MTs), 5 clusters, and 25 singletons. MLST results for tigecycline-resistant isolates showed seven different STs. Increasing antibiotic resistance in A. baumannii isolates requires careful management to control and prevent the occurrence of the pre-antibiotic era. The results of this study confirm that the population structure of A. baumannii isolates has a high diversity. More extensive studies are needed in Iran to better understand the epidemiology of A. baumannii.